Konsep iman kepada hari akhir perspektif Imam Al-Qurthubi dalam kitab Al-Tazkirah bi Ahwal Al-Mauta wa Umur Al-akhirah - Shian, Fahrurrozi bin Naksi; Hafidhuddin, Didin; Rahman, Imas Kania (Tawazun: Jurnal Pendidikan Islam, 2023)
Individual attitudes and behavior are closely related to faith in Allah and the Judgment Day. The destruction of morals, the chaos of people's lives in various fields, indicate the weakness of individual faith which can result in the collective destruction of a society, even a nation. For this reason, preventive measures are needed in the form of strengthening faith in the judgment day. This research is intended to reveal the concept of strengthening faith towards the judgment day according to Imam Al-Qurtubi in the book al-tadzkirah bi ahwal al mauta wa umur al-akhirah and its relevance to the teaching material on the theme of faith towards the judgment day. The method used in this research is a qualitative method with a library research approach. Data analysis was carried out using content analysis, descriptive and inductive techniques. Based on the results of the study it was found that the concept of strengthening faith on the last day according to Al-Qurtubi includes: al-maut (the death), al-barzakh (the grave), al-ba'ts (the resurrection day), al-jaza' (the rewards of deeds). and asyrath al-sa'ah (signs of the Day of Judgment). These findings deserve to be suggestion in improving the concept of strengthening faith in the day of judgment for the elderly in the guidance and counseling program Abstrak Sikap dan perilaku individu berkaitan erat dengan iman kepada Allah dan hari akhir. Rusaknya moral, carut marutnya kehidupan masyarakat di berbagai bidang, mengindikasikan lemahnya keimanan individu yang dapat mengakibatkan kerusakan kolektif suatu masyarakat, bahkan sebuah bangsa. Untuk itu dibutuhkan langkah preventif berupa penguatan iman kepada hari akhir. Penelitian ini ditujukan guna mengungkap konsep penguatan iman kepada hari akhir menurut imam Al-Qurthubi dalam kitab Al-Tadzkirah bi Ahwal Al-Mauta wa Umur Al-Akhirah dan relevansinya dengan materi ajar tema iman kepada hari akhir. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan study pustaka (library research). Analisis data dilakukan dengan teknik analisis isi (content analysis), deskriptif dan induktif. Berdasarkan hasil penelitian ditemukan bahwa konsep penguatan iman pada hari akhir menurut Al-Qurthubi meliputi: al-maut (kematian), al-barzakh (alam kubur), al-ba’ts (hari berbangkit), al-jaza’ (balasan amal) dan asyrath al-sa’ah (tanda-tanda hari kiamat). Temuan tersebut layak menjadi masukan dalam penyempurnaan konsep penguatan iman kepada hari akhir bagi lansia dalam program bimbingan dan konseling.